From sound to synapse : - Geisler, C. Daniel (Oxford University Press, 1998)
This comprehensive introduction to the functions of the mammalian ear describes the major steps by which sound is transformed into nerve impulses. The author leads the reader along the pathway followed by the acoustic signal. He starts with the collection of sound by the outer ear, proceeds to its transfer by the middle ear, and finally analyzes its modification in the inner ear, where the sound waves are transformed into nerve impulses. The book concludes with descriptions of some common ear impairments and a brief survey of the treatments available for them.